Influence of the type of phase change materials microcapsules on the properties of lime-gypsum thermal mortars - Cunha, Sandra Raquel Leite (2014)
In a society with a high growth rate and increased standards of comfort arises the need to minimize the currently high energy consumption by taking advantage of renewable energy sources. The mortars with incorporation of phase change materials (PCM) have the ability to regulate the temperature inside buildings, contributing to the thermal comfort and reduction of the use of heating and cooling equipment, using only the energy supplied by the sun. However, the incorporation of phase change materials in mortars modifies its characteristics. The main purpose of this study was the production and characterization of mortars with incorporation of two different phase change materials. Specific properties of two phase change materials, such as particle size, shape and enthalpy, were determined, as well as the properties of the fresh and hardened state of the mortars. The proportion of PCM was 0%, 10%, 20% and 30% of the total mass of the solid particles. In order to minimize some problems associated with shrinkage and consequent cracking of the mortars, the incorporation of polyamide fibers and superplasticizer was tested. It was possible to observe that the incorporation of phase change materials in mortars caused differences in properties such as compressive strength, flexural strength and shrinkage. Even though the incorporation of PCM microcapsules resulted in an increase in the shrinkage, it was possible observe a significant improvement in mechanical properties.